Linked fate, cumulative discrimination, and panethnic identification: awareness and use of 'Latinx' among a nationally representative sample of Hispanics/Latinos. Issue 19 (4th November 2022) - Thompson, Jack; Martinez, Daniel E.
ABSTRACT: 'Latinx' – a gender neutral variation of 'Latino', is increasingly used to describe individuals of Latin American origin in the United States. Drawing on data from the 2019 National Survey of Latinos, we assess familiarity, use, and attitudes towards the term Latinx among Hispanic-Latinos. We find that linked fate, discrimination experiences, being a Democrat, being younger, and higher levels of education predict greater awareness of the term. Having ever used Latinx to identify oneself is only associated with discrimination experiences, identifying as Afro-Latino, and being female. However, the effects of discrimination experiences on having ever used the term are moderated by immigrant generation and age. Meanwhile, believing the term should be used as a panethnic label is associated with the same factors as those that explain awareness of the term, with the exception of greater education. Lastly, we find that the factors associated with preferences for 'Latinx' over both 'Hispanic' and 'Latino' are similar, suggesting that those who prefer the term represent a distinct subgroup of Hispanic-Latinos. Collectively, our findings suggest that, while college campuses represent critical sites for raising awareness of the term, this knowledge is not necessarily leading to its active use among Hispanic-Latinos themselves.